A conferência de Durban e as políticas públicas para combate às desigualdades étnico-raciais: - Vizolli, Iaraí (Universidade Federal do Tocantins, 2023)
This monograph aims to analyze the Durban Conference held in South Africa in 2001, aiming to understand how the guidelines present at the Conference influenced the construction of Public Policies to promote racial equality in Brazil from 2001 on. The research has a qualitative nature and is divided into two main stages: bibliographic and documentary. The work has three chapters. The first discusses some concepts such as racism, colonialism, postcolonial theory, decolonial and the UN International Regime to Combat Racism and Racial Discrimination. The second chapter presents the Durban Convention, regional preparations, main points of tension, as well as its greatest achievements. Chapter three deals with public policies aimed at racial equality created and implemented in Brazil after the Convention, namely: SEPPIR, the Racial Equality Statute and Affirmative Actions. On the final considerations, it was found that the Durban Conference was one of the crucial points for the fight to end racial prejudice and discrimination in the world. However, there is still a long way to achieve equality of all human beings without distinction.